Islamic code of conduct for mediation: a case study of the code of conduct of Malaysian Mediation Centre (MMC) - Amanullah, Muhammad (2015)
The courts of every country are so overwhelmed by so many different types of cases submitted by their clients that these courts cannot settle them timely and also the related procedures are very costly. In order to help the public and to some extent the governments, alternative means of solving the conflicts and disputes are well established and practiced all over the world. One of these means is to solve the disputes through mediation. Many organizations, centers, etc. have been established for mediation all over the world. These organizations have tried to produce the code of conducts for mediation. One of these organizations is Malaysian Mediation Centre. This center has wide range of activities. In order to practice the mediation properly, this center, like many other organizations, produced its code of conducts. Because of some external factors, some Muslims have some doubt about the credibility of mediation. Islam has also prescribed many principles of mediation which combinedly may be called as “Islamic Code of Conduct for Mediation.” As per the knowledge of the researcher, no comprehensive Islamic code of conduct for mediation has been written in English. In the past and to some extent even now the mediation for family affairs and other simple issues has been conducted by the imams of the mosques or influential leaders of the society. But nowadays it has become a well-established profession, for which, like any other professions, there is a need to produce such a code. On the other hand, an evaluation of MMC’s code of conduct in light of Islamic code of conduct for mediation is required to find out whether MMC’s code is complete and suitable for this purpose, or it still needs modifications. Using analytical, critical and comparative methods and depending on the verses of the Qur’an and ahadith of the Prophet (p. b. u. h.) and statements of Muslim scholars, this research paper attempts to focus on producing a comprehensive Islamic code of conduct for mediation and evaluating the code of conduct of MMC. Therefore, this paper is divided into following sections: introduction, methodology and guidelines of writing this ode, Islamic code of conduct for mediation, evaluation of the code of conduct of Malaysian Mediation Centre (MMC) and suggestions to improve MMC’s code of conduct, and a conclusion.